2006
DOI: 10.1111/j.1742-7843.2006.pto_369.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Motor Effects of ATP and their Inhibition by P2 Purinoceptor Antagonist, Pyridoxalphosphate‐6‐azophenyl‐2′,4′‐disulphonic Acid in the Small Intestine of the Guinea‐Pig

Abstract: Adenosine 5ø-triphosphate (ATP) may be an important neurotransmitter in the gastrointestinal tract. The present study examined the motor effects of exogenous ATP on longitudinally-oriented preparations of the guinea-pig isolated ileum and the influence of drugs on the ATP-induced responses. High micromolar concentrations of ATP caused two types of contraction, a phasic, cholinergic response and a tonic, tetrodotoxin-resistant contraction. The phasic contraction was reduced by hexamethonium (5¿10 ª5 M), but lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…In the myenteric plexus, all enteric neurons, except NO synthase (EC 1.14.13.39)‐immunoreactive inhibitory muscle motoneurons, contain choline acetyltransferase (EC 2.3.1.6) (Furness, 2000), suggesting that myenteric neurons are mostly cholinergic and that ATP and ACh might be co‐released. Here, we provided evidence indicating that cholinergic nerve terminals of the myenteric plexus of the rat ileum possess TNP‐ATP‐sensitive P2X receptors triggering the release of [ 3 H]ACh in the absence of action potential generation (see also Barthó et al. , 2006).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the myenteric plexus, all enteric neurons, except NO synthase (EC 1.14.13.39)‐immunoreactive inhibitory muscle motoneurons, contain choline acetyltransferase (EC 2.3.1.6) (Furness, 2000), suggesting that myenteric neurons are mostly cholinergic and that ATP and ACh might be co‐released. Here, we provided evidence indicating that cholinergic nerve terminals of the myenteric plexus of the rat ileum possess TNP‐ATP‐sensitive P2X receptors triggering the release of [ 3 H]ACh in the absence of action potential generation (see also Barthó et al. , 2006).…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that purinergic neurotransmission may be mediated by cholinergic neurons (Matsuo et al. , 1997; Barthó et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…[52-54] Thus, antagonism of both P2X and P2Y receptors by PPADS may explain the prolongation of PCr half-life observed in our study.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, it is known that α,β-Me-ATP application leads to neural fiber-mediated cholinergic contractions [5] , and altered ATP release from cholinergic fibers in response to pre-junctional P2Y receptor activation may have occurred in our preparations [8] . Therefore, we examined the P2Y receptor-induced transient relaxation following preincubation with atropine, L-NAME or TTX and found that at least the P2Y receptor-mediated relaxation was independent of acetylcholine or nitric oxide release from pre-junctional nerve fibers.…”
Section: Wwwchinapharcom Mader F Et Almentioning
confidence: 99%
“…While NO leads to a long-lasting inhibition of smooth muscle motility, the available data on purinergic responses are less consistent, as both excitatory and inhibitory effects have been observed and seem to depend on the subtype and cellular location of P2 purinoceptors. In addition, species differences should also be considered [2][3][4][5][6][7][8][9][10] . Seven cloned ionotropic P2X receptors that combine heteromerically, as well as eight cloned metabotropic P2Y receptors, account for the large heterogeneity of purinoceptormediated effects [11] .…”
Section: Introductionmentioning
confidence: 99%